HUBUNGAN STATUS EKONOMI KELUARGA DENGAN PERILAKU PENGOBATAN SENDIRI (SELF-MEDICATION) - Utari, Dewi; Setiono, Wiwing (Universitas Jenderal Achmad Yani Yogyakarta, 2016)
Background: Health degree is an important component of health development. One of the indicators is morbidity rate. Based on National Health Survey in 2008, the number of morbidity rate is 33.24% where 65.59% of population applied self-medication to treat their health problems. Many factors influence people to use self-medication. Family economic status is suspected to be one of them. Objective: This study aimed to identify the correlation between family economic status and self-medication behavior. Methods: A quantitative cross sectional design study with retrospective approach was applied. Cluster random sampling technique was employed to 71 respondents. The Kendall Tau test was performed to analyze the data. The probability risk factors of self-medication was identified using odds ratio. Results: The family economic status were gained with 81.7% in high category and 15.5% in low category. The result of self-medication behavior showed 69% of the respondents often did self-medication, 15.5% rarely, and 15.5% never. The Kendall Tau correlation was 0,515 (p<0.05) and the odds ratio was 8,941. Conclusion: There is a moderate correlation between family economic status and self-medication behavior where the family with high economic status is more likely implement self-medication 8,941 times more than the one with low economic status. Keywords: Economic Status, Family, Behavior, Self-Medication